The influence of career guidance on students' subject selection at " Ordinally" level schools in Katakwi district - Opul, Joseph (Kampala, 2013)
Un published dissertation (M.Ed. FOUND & MGT) - Makerere University, 2013.
Includes bibliographical references.
Keywords: Vocational guidance -- Uganda -- Katakwi district